Judgment Method of the Electromagnetic (EM) Communication between Mobile Phone Antennae and Human Body: Evaluation of EM Interaction between Mobile Phone Antenna and Human Body (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This article presents a detail method for the evaluation of the Electromagnetic interaction between the mobile phone antenna and human body, i.e., head and hand, and inspect the factors may influence this communication. These factors are considered for different mobile phone handset models, different form factors and different antenna types, operating in the GSM900, GSM1800/DCS, and UMTS/IMT- 2000 bands. A realistic usage of mobile phone handset next to head at cheek and tilt positions, in compliance with IEEE-standard152, is considered during computations. Homogeneous and heterogeneous CAD- models are used to simulate the mobile phone user’s head, whereas, a homogeneous model with three different tissues is designed to simulate the user's hand-hold. A validation of our EM interaction computation using bothYee-FDTD and ADI-FDTD is achieved by comparison with previously published works.